Lenora de Barros: poesia expandida - Lima, Hélida de (2017)
In 1970, in the context of the experimental cinema of the time, Gene Youngblood released a book under the title of Expanded Cinema. It took a few decades for this text to be repeatedly remembered and quoted. From about ten years on, the adjective "expanded" began to be increasingly attached to other media, especially photography and even video. This is most probably due to the growing process of hybridization of languages as a consequence of the multiplication of media we are seeing. This is the background of this research. At the forefront, there is the search for exploitation of the production of the artist and poet Lenora de Barros. For this reason, it was imperative to return to a cultural universe, since her work comprises an extension of the operations put in by Concrete Poetry and Neoconcretism, since the 1970s. So much so that the artist uses post- Duchamp positions, entangled rock, pop, paradigmatic changes on the body, the rise of performance art and video art. Thus, it is proposed to rewrite an "Other Generation 80". The corpus of the research is understood by the works: Poema (1979), Língua Vertebral (1998) and the series Não Quero Nem Ver (2005). Therefore, the research questions: How to name, in order to understand and signify, a quantity of multiple performances contained within your creation? With this in mind, the concept of "Expanded Poetry" is developed here. The theoretical foundation is fixed on the understandings of semiosis and aesthetic sign, contextualized in the light of the semiotic philosophy of Charles Sanders Peirce